Television today and yesterday, perspectives and challenges - Garcia Toledo, Magdalena (2009)
The anide presents two perspectives regarding che television phenomenon in what respects to media consumption and ics impact on che social and cultural fields of our society. The first perspective is about television as a massive phenomenon crossed by the theories of reception developed above all in Latin America. The second perspeccive is about the presente and development of digital relevision which is expected to revolucionize not only the personal and sociallife of che public but also che economic, political, cultural and educative systems in our societies